Ropivacaine 75 mg versus placebo in perineal infiltration for analgesic efficacy at mid- and long-term for episiotomy repair in postpartum women – the ROPISIO study: a two-center, randomized, double-blind, placebo-controlled trials - Claire Cardaillac; Stéphane Ploteau; Aurélie Le Thuaut; Vincent Dochez; Norbert Winer; Guillaume Ducarme (Trials, 2020)
Abstract Background Perineal pain due to episiotomy is commonly reported and can be severe enough to disturb the mother–infant dyad during the postpartum period. Its incidence at day 7 postpartum varies from 63% to 74%. Recent studies have investigated the analgesic efficacy of perineal infiltration of ropivacaine after episiotomy but have only focused on the immediate postpartum period (at 24 and 48 h after birth). Large, adequately powered, multicenter, randomized controlled trials are required to evaluate the impact of ropivacaine infiltration on perineal pain and mid- and long-term quality of life before the widespread use of ropivacaine to prevent perineal pain after episiotomy can be recommended. Methods/design The ROPISIO study is a two-center, randomized, double-blind, placebo-controlled trial being conducted in La Roche sur Yon and Nantes, France. It will involve 272 women with vaginal singleton delivery and mediolateral episiotomy at term (≥ 37 weeks). Perineal infiltration (ropivacaine 75 mg or placebo) will be administrated just after vaginal birth and before episiotomy repair. The primary outcome will be the analgesic efficacy at day 7 postpartum (midterm), defined by the Numeric Pain Rating Scale (NPRS) strictly superior to 3/10 on the perineal repair area. Secondary outcomes will be the analgesic efficacy (NPRS) and the impact of pain on daily behavior, on the quality of life (36-item Short Form Health Survey), on the occurrence of symptoms of postpartum depression (Edinburgh Postnatal Depression Scale), and on sexual health (Female Sexual Function Index) at 3 and 6 months (long-term) using validated online questionnaires. This study will have 90% power to show approximately 30% relative risk reduction in the incidence of perineal pain at day 7, from 70.0% to 50.0%. Discussion Ropivacaine is a promising candidate drug, inexpensive, and easy to administer, and it would be suitable to include in the routine management of deliveries in labor ward. This study will investigate if perineal ropivacaine infiltration just after birth can reduce mid- and long-term postpartum pain and increase quality of life in women with mediolateral episiotomy. Trial registration ClinicalTrials.gov, NCT03084549 . Registered on 14 April 2017.